1982
DOI: 10.1016/0014-5793(82)81086-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for erythrocyte membrane glycoproteins being carriers of blood‐group P1 determinants

Abstract: The contribution of different membrane constituents to the bloodgroup P1 activity of human erythrocytes was investigated. Pronase digestion of native red cell stroma or partition between butanol and water had no serologically detectable effect, whereas pronase‐treatment of previously butanol‐extracted membranes liberated virtually all blood‐group P1 determinants from the ghosts. On Laemmli gels, all P1 activity was found in the band 4.5 region. Thus it is concluded that, in addition to the well‐documented P1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One view that remained largely unchallenged for over 20 years was that the human Gb3/CD77 synthase (α1,4-galactosyltransferase, P1/P k synthase; EC 2.4.1.228) could only use GSLs as acceptors to produce Gal-α1→4Gal-terminated glycans (Gb3 and P1). The presence of P1 glycotope on human glycoproteins was first suggested by (36) and tested by (37), who reported that P1-antiserum recognized band 4.5 (GLUT1) and, to a lesser extent, other erythrocyte membrane proteins. However, a subsequent study contradicted those results by showing a complete depletion of P1 determinants from erythrocyte membrane glycoproteins upon treatment with n-butanol (38).…”
Section: Discussionmentioning
confidence: 94%
“…One view that remained largely unchallenged for over 20 years was that the human Gb3/CD77 synthase (α1,4-galactosyltransferase, P1/P k synthase; EC 2.4.1.228) could only use GSLs as acceptors to produce Gal-α1→4Gal-terminated glycans (Gb3 and P1). The presence of P1 glycotope on human glycoproteins was first suggested by (36) and tested by (37), who reported that P1-antiserum recognized band 4.5 (GLUT1) and, to a lesser extent, other erythrocyte membrane proteins. However, a subsequent study contradicted those results by showing a complete depletion of P1 determinants from erythrocyte membrane glycoproteins upon treatment with n-butanol (38).…”
Section: Discussionmentioning
confidence: 94%
“…Studies supporting both ideas have been published. 6,7 In a recent study from our laboratory, the ability of P1P k synthase to use acceptors on both types of carriers was supported by the detection of P1 on human RBC glycoproteins. We also showed a dosage-dependent effect of A4GALT genotype on the level of P1 staining of RBC membrane proteins and, in addition, reported data supporting the idea that P1 appeared to be mainly carried on N-glycans in glycoproteins.…”
Section: Biochemistrymentioning
confidence: 92%
“…It has been debated whether the P k and P1 antigens exist on glycoproteins present in the human RBC membrane or if glycolipids are the only membrane components carrying these epitopes [47,48]. However, a recent publication showed evidence that the P1 antigen can be detected on human RBC glycoproteins [49].…”
Section: Biochemistrymentioning
confidence: 99%